2020
DOI: 10.1017/jrr.2020.15
|View full text |Cite
|
Sign up to set email alerts
|

The Investment Model: Its Antecedents and Predictors of Relationship Satisfaction

Abstract: Intimate relationships are an integral part of our lives, but the rate of relationship breakups is high. We explored the role of the investment model and the traits that influence investments on relationship satisfaction among 146 volunteers (age M = 28.76 years, SD = 10.23). Relationship satisfaction was predicted by investments, which in turn were predicted by attachment, personality and love style. Clinicians working with individuals or couples with relationship issues may benefit from knowing how invested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Moreover, consistent with H1, the results from Study One indicated that those who endorsed idealized first kiss beliefs to a greater extent also reported being more in love with their current romantic partner than those endorsing these beliefs to a lesser extent. This relationship aligns and extends existing literature that has identified an association between idealized romantic belief endorsement and higher relationship satisfaction ( Vannier and O’Sullivan, 2017 ; Kretz, 2019 ), which has been positively associated with love ( Hendrick et al, 1988 ; Morrow et al, 1995 ; Vedes et al, 2016 ; Moore and Campbell, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, consistent with H1, the results from Study One indicated that those who endorsed idealized first kiss beliefs to a greater extent also reported being more in love with their current romantic partner than those endorsing these beliefs to a lesser extent. This relationship aligns and extends existing literature that has identified an association between idealized romantic belief endorsement and higher relationship satisfaction ( Vannier and O’Sullivan, 2017 ; Kretz, 2019 ), which has been positively associated with love ( Hendrick et al, 1988 ; Morrow et al, 1995 ; Vedes et al, 2016 ; Moore and Campbell, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…5 This relationship aligns and extends existing literature that has identified an association between idealized romantic belief endorsement and higher relationship satisfaction (Vannier and O'Sullivan, 2017;Kretz, 2019), which has been positively associated with love (Hendrick et al, 1988;Morrow et al, 1995;Vedes et al, 2016;Moore and Campbell, 2020).…”
Section: Fkbs Scale Items M (Sd)supporting
confidence: 82%
See 1 more Smart Citation
“…The sense that one's partner is investing in the relationship indicates that they are prepared to satisfy the other partner's needs (Moore & Campbell, 2020). Specific investments in a relationship comprise contributions that “individuals bring to a relationship or do in a relationship that influences their exchange value to the partner” (Ellis, 1998, p. 384).…”
Section: The Impact Of Relationship Investment Tactics On Relationshi...mentioning
confidence: 99%
“…This commitment increases as relationship satisfaction increases, and also as the quality of alternatives diminishes and as greater relationship investments are made (Tran et al, 2019). Rusbult and colleagues found a significant correlation between partners' perceived investment in their relationship and the relationship duration, and the partners' commitment to and satisfaction with it (Rusbult et al, 1986, as cited in Moore & Campbell, 2020). Predictive models of relationship satisfaction indicate that individuals experience relationship satisfaction when their basic needs, such as affection and companionship, are fulfilled in these relationships.…”
Section: The Impact Of Relationship Investment Tactics On Relationshi...mentioning
confidence: 99%